The Welfare effects of direct-to-consumer salese - Yoshida, Renan Chaves (2019)
Cutting off the intermediary and selling directly to consumers is an increasingly common strategy by manufacturers in many industries. Its impact on prices, profits and consumer welfare is theoretically ambiguous. It leads to an increase in competition and a larger variety of products, which tends to lower prices and increase consumer welfare. However, it may also strengthen manufacturers’ bargaining leverage when negotiating fees with retailers, which pressures prices upward, potentially offsetting the competition effect and the gains from variety. To understand and quantify this trade-off we use data on the outdoor advertising industry, which permits us to estimate demand for advertising products and a model of wholesale price bargaining and downstream price setting. We then simulate the removal of the direct-to-consumer channel in various scenarios to disentangle the effects above. We find that they are significant, though the competition effect dominates. The effect of directto-consumer sales in our setting is lower prices, higher manufacturer profits, lower retailer profits, higher consumer welfare and total welfare.